2022
DOI: 10.3390/ime1010003
|View full text |Cite
|
Sign up to set email alerts
|

Management of Malpositioned Double-Lumen Tubes: A Simulation-Based Training Exercise for Anesthesiology Residents

Abstract: Objectives: Demonstrate the feasibility and effectiveness of using the AirSim® Bronchi airway simulator to teach anesthesia residents how to successfully troubleshoot and manage malpositioned double-lumen endotracheal tubes used for single-lung ventilation. Design: Prospective observational study. Setting: Simulation lab in a university-based anesthesiology residency training program. Participants: CA1 (PGY2) anesthesiology residents. Interventions: Each resident was initially tasked with troubleshooting a mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Furthermore, residents can attend several national and international meetings and are involved in variety research projects. In addition, inside the school network, there are also two high-fidelity simulation labs where is possible to implement technical and non-technical skills, has it happened for other disciplines [3,[18][19][20][21][22]. Thanks to all these resources, the school of Modena is accredited by MIUR and currently trains 147 residents, and it has played a strategic role, as reservoir of physicians with a degree of training in A-IC of UNIMORE during many stressful system events such as Emilia-Romagna region (Italy) earthquake in 2012, and during the Vasco Rossi Modena Park ® concert with about 220.000 participants and about 5000 staff members [7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, residents can attend several national and international meetings and are involved in variety research projects. In addition, inside the school network, there are also two high-fidelity simulation labs where is possible to implement technical and non-technical skills, has it happened for other disciplines [3,[18][19][20][21][22]. Thanks to all these resources, the school of Modena is accredited by MIUR and currently trains 147 residents, and it has played a strategic role, as reservoir of physicians with a degree of training in A-IC of UNIMORE during many stressful system events such as Emilia-Romagna region (Italy) earthquake in 2012, and during the Vasco Rossi Modena Park ® concert with about 220.000 participants and about 5000 staff members [7].…”
Section: Discussionmentioning
confidence: 99%
“…Hierlmeier et al . [ 23 ] studied the effect of SBT in troubleshooting the malpositioned DLT in ten anesthesiology residents. It showed that the time to correct the position of DLT and the percentage of trainees who could correct the position of DLT successfully improved after two simulation-based sessions and didactic presentations.…”
Section: Introductionmentioning
confidence: 99%